2018
DOI: 10.1038/s41398-018-0320-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurostructural correlate of math anxiety in the brain of children

Abstract: Adequate mathematical competencies are currently indispensable in professional and social life. However, mathematics is often associated with stress and frustration and the confrontation with tasks that require mathematical knowledge triggers anxiety in many children. We examined if there is a relationship between math anxiety and changes in brain structure in children with and without developmental dyscalculia. Our findings showed that math anxiety is related to altered brain structure. In particular, the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
4
28
0
6
Order By: Relevance
“…Anxiety is one of the most prevalent mental health problems among children ( 1 , 2 ), with an estimated prevalence up to 20% ( 3 , 4 ). Anxiety in children has a negative impact on their school performance ( 5 ), social functioning ( 6 ), and quality of life ( 7 ). In addition, anxiety symptoms during childhood tend to be chronic and may lead to anxiety disorders and other serious psychopathological consequences that persist into later childhood and adulthood ( 1 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is one of the most prevalent mental health problems among children ( 1 , 2 ), with an estimated prevalence up to 20% ( 3 , 4 ). Anxiety in children has a negative impact on their school performance ( 5 ), social functioning ( 6 ), and quality of life ( 7 ). In addition, anxiety symptoms during childhood tend to be chronic and may lead to anxiety disorders and other serious psychopathological consequences that persist into later childhood and adulthood ( 1 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning math achievement, both groups (high and low anxious children, grade 3) improved their performance in an arithmetic problem solving task equally, as there was no interaction with math anxiety level. Recent work by Kucian et al (2018a) has demonstrated that math anxiety is even related to changes in brain structure. Particularly, the volume of the amygdala was reduced, which represents the key area in our brain for negative emotional processing such as fear, stress and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…These parts can influence students' cognitive processes in classroom. The prefrontal cortex is the part of the brain that processes information for a high level of reasoning while the amygdala records emotions or situations in life [29,7,11,12]. From the findings of the neuroscience research, the researchers will discuss in more detail; the results of this study can be applied in the context of learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotion plays an important role in stimulating cognitive especially memory to learn [9,10]. The reason is that emotions in learning can affect brain regions such as the prefrontal cortex which is important for thinking and reasoning as well as the hippocampus that plays important roles in consolidation of information memory [9,11,12]. This information can increase the knowledge gap in educators to understand the role of emotion and its effect on student's brain and at the same time overcome the students' emotional problem in learning Mathematics [10,13,14].…”
Section: Introductionmentioning
confidence: 99%